2019
DOI: 10.1136/bjophthalmol-2019-314377
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nine previously reported and 10 non-reported SLC4A11 mutations among 20 Iranian CHED probands and identification of an MPDZ mutation as possible cause of CHED and FECD in one family

Abstract: Background/aimsSLC4A11 is the only known causative gene of congenital hereditary endothelial dystrophy (CHED). Mutation screenings have shown that most but not all patients with CHED harbour mutations in SLC4A11, suggesting that other CHED-causing genes may exist. We aimed to screen SLC4A11 in Iranian patients to learn the mutation spectrum of this gene among Iranians and to gain further knowledge on potential contribution of other genes to CHED aetiology.MethodsSLC4A11 was screened in 21 Iranian patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Approximately 94 SLC4A11 mutations have been identified in individuals with CHED. 4,6,9,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Although a large number of these mutations result in SLC4A11 protein misfolding and failure to mature to the plasma membrane, 5,6,[49][50][51] some mutations affect SLC4A11 transporter function without impacting membrane trafficking 17,52,53 or cause aberrant SLC4A11 pre-mRNA splicing and subsequent reduced SLC4A11 expression. 47 Collectively, these observations support the hypothesis that loss of SLC4A11 function is the primary pathogenetic mechanism in CHED rather than mutant SLC4A11 protein misfolding/mislocalization in the endoplasmic reticulum (ER).…”
mentioning
confidence: 99%
“…Approximately 94 SLC4A11 mutations have been identified in individuals with CHED. 4,6,9,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Although a large number of these mutations result in SLC4A11 protein misfolding and failure to mature to the plasma membrane, 5,6,[49][50][51] some mutations affect SLC4A11 transporter function without impacting membrane trafficking 17,52,53 or cause aberrant SLC4A11 pre-mRNA splicing and subsequent reduced SLC4A11 expression. 47 Collectively, these observations support the hypothesis that loss of SLC4A11 function is the primary pathogenetic mechanism in CHED rather than mutant SLC4A11 protein misfolding/mislocalization in the endoplasmic reticulum (ER).…”
mentioning
confidence: 99%
“…The patient did not have the SLC4A11 mutation. The mother carrying the MPDZ gene variation had a mild FECD phenotype, a phenomenon seen in patients with the SLC4A11 gene [ 38 ]. However, evidence for MPDZ in SLC4A11 negative cases is scarce and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…CHED is common among people in India, Saudi Arabia, and Iran. Several studies have shown that nearly 100% of the CHED patients had mutations in Slc4a11 [31][32][33] . There are several SLC4A11 mutations associated with CHED 8,31,34 .…”
Section: Discussionmentioning
confidence: 99%